HALLIWICK CONCEPT AND ENGAGEMENT OF CHILDREN WITH DISABILITIES (Fiep Bulletin - online, 2016)
The aim was to analyze the time of engagement of children with disabilities in the context of Adapted Motor Activity, by the Halliwick concept. The participants were five children with disabilities. For data collection was performed and filmed a class based on Halliwick, in which it was registry in written. For the analysis of the data it was used: a) Class time: 1) Class - total class time, activity time and transition time and, 2) The time of engagement of children in activity - out of focus, in occupation or wasted time. The total allotted time was 37 minutes and 21 seconds long, 4 minutes and 49 seconds corresponding to transitions between the activities and 32 minutes and 32 seconds to actual tasks carried out according to the method suggested by Halliwick. As for the time of engagement of the children, the average was 6 minutes and 7seconds out of focus. The average occupation time was 25 minutes and 2 seconds and of wasted time of 1minute and 23 seconds. The activities that showed higher occupancy time were 9 (get out of the water by the ramp) and 2 (blowing water and soap to make bubbles), being 96,7% and 86,7% of activity time, respectively. The activity with lower average occupancy time was 5 (collect balls and keep them in a basket), equivalent to 45,7%. It was notice that the application of the Halliwick concept provided the children to remain occupied for long periods and the wasted time was reduced. Linked to Halliwick concepts, preplanning class and the professional preparation are essential components for a good time management in class and the good performance of all students.
Keywords: Halliwick; engagement; children with disabilities.